Guiding Binocular Saccades during Reading: A TMS Study of the PPC - VERNET, Marine; YANG, Qing; KAPOULA, Zoi (Frontiers in Human Neuroscience, 2011)
Reading is an activity based on complex sequences of binocular saccades and fixations. During saccades, the eyes do not move together perfectly: saccades could end with a misalignment, compromising fused vision. During fixations, small disconjugate drift can partly reduce this misalignment. We hypothesized that maintaining eye alignment during reading involves active monitoring from posterior parietal cortex (PPC); this goes against traditional views considering only downstream binocular control. Nine young adults read a text; transcranial magnetic stimulation (TMS) was applied over the PPC every 5±0.2 sec. Eye movements were recorded binocularly with Eyelink II. Stimulation had three major effects: (1) disturbance of eye alignment during fixation; (2) increase of saccade disconjugacy leading to eye misalignment; (3) absence of eye alignment reduction during fixation drift. The effects depend on the side; the right PPC was more involved in maintaining alignment over the motor sequence. Thus, the PPC is actively involved in the control of binocular eye alignment during reading, allowing clear vision. Cortical activation during reading is related to linguistic processes and motor control per se. The study might be of interest for the understanding of deficits of binocular coordination, encountered in several populations, e.g. in children with dyslexia.